Upliftment of the Marginalized in India: A Study of the Muslim Empowerment Through Islamic Social Finance - Wani, Athar Shahbaz (Journal of Muslim minority affairs, 2022)
India being a dynamic emerging economy, with religious and cultural diversity, is home to 0.172 billion Muslims, that is 14.2 percent of the population at all India level living as the financially excluded minority community in the country. The Indian Muslims according to Sachar Committee Report (2005) are the financially ‘excluded’ community and are not the major beneficiary of Govt. schemes.” The Reports/Commissions such as Ranganathan Misra Committee (2007); Mahmoodur Rahman Committee (2008); Sudhir Commission Report (2016) and Commission of Inquiry (Telangana 2016), reveal that Muslims in India, are living in pathetic conditions with underdeveloped socio-economic and educational setup. In this context, the current paper aims to-explore through qualitative analysis the possible dimensions of social finance and to evaluate the current socio-economic conditions of Muslims in India. This study will be an attempt to assess the potential of Islamic social finance institutions, namely the zakat and the waqf, for community upliftment in a much broader national context.